2003
DOI: 10.2337/diabetes.52.5.1176
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Islet Somatostatin Regulates Glucagon Release via Type 2 Somatostatin Receptors in Rats

Abstract: Exogenously administered somatostatin (SST) inhibits secretion of insulin and glucagon. Furthermore, it is hypothesized that islet SST regulates glucagon secretion by a local action. A number of studies utilizing SST antibodies have been performed to test this hypothesis, and their results have been conflicting. Five subtypes of SST receptor (SSTR1-5) mediate the effect of SST on target cells. In rodents, SST inhibits the release of glucagon, but not that of insulin, via SSTR2. A novel SSTR2-selective antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 45 publications
3
90
2
Order By: Relevance
“…Also in line with these studies, no effect of GLP-2 on insulin secretion was observed. It is well established that somatostatin inhibits glucagon secretion in the endocrine pancreas, and we have recently shown that GLP-1 mediates its inhibitory effect on the pancreatic alpha cell through somatostatin acting on somatostatin receptor subtype 2 (J. de Heer, D. H. Coy, J. J. Holst, unpublished results) [19][20][21]. However, in the present study the release of somatostatin was unaltered in response to GLP-2.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Also in line with these studies, no effect of GLP-2 on insulin secretion was observed. It is well established that somatostatin inhibits glucagon secretion in the endocrine pancreas, and we have recently shown that GLP-1 mediates its inhibitory effect on the pancreatic alpha cell through somatostatin acting on somatostatin receptor subtype 2 (J. de Heer, D. H. Coy, J. J. Holst, unpublished results) [19][20][21]. However, in the present study the release of somatostatin was unaltered in response to GLP-2.…”
Section: Discussioncontrasting
confidence: 55%
“…The influence of GLP-2 alone and in combination with GLP-1 on glucagon secretion was examined in the isolated perfused rat pancreas. In addition, we evaluated the effect of GLP-2 on the secretion of other islet hormones, as both insulin and somatostatin have been implicated in the regulation of glucagon release [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A study with an SSTR2 antagonist DC-41-33 potentiated the rise of arginine-stimulated glucagon secretion at low glucose and antagonized SST-dependent inhibition of glucagon secretion in rat pancreatic islets confirmed the role of SSTR2 as an inhibitor of glucagon secretion (Cejvan et al, 2003). The effects of DC-41-33 on insulin secretion were much less potent.…”
Section: Antagonistsmentioning
confidence: 74%
“…DC-41-33 is an SSTR2-specific antagonist having 9-21 times lower affinity for SSTR3 and SSTR5 (Hocart et al, 1999;Rossowski et al, 1998). In perifused islets DC-41-33 more potently enhanced the maximal and the arginine-stimulated second phase of glucagon secretion, as compared to its effects on insulin secretion (Cejvan et al, 2003). While the effects on glucagon are clearly SSTR2-dependent, the moderate stimulation of insulin secretion suggests that SSTR2 may be involved in regulating insulin secretion.…”
Section: Antagonistsmentioning
confidence: 99%
“…There is evidence that substances including Zn 2+ [5], γ-aminobutyric acid (GABA) [6][7][8] released from beta cells and somatostatin secreted from neighbouring delta cells [9] have important roles in the modulation of glucagon secretion. Thus, it has been proposed that glucose may induce suppression of glucagon release by indirect actions via a paracrine mechanism.…”
mentioning
confidence: 99%